A vehicle social distancing management system based on LiFi COVID pandemic: real-time monitoring for smart buildings - Murad, Sallar S.; Yussof, Salman; Oraibi, Bha-Aldan Mundher; Badeel, Rozin; Badeel, Banan; Alamoodi, A. H. (Institute of Electrical and Electronics Engineers, 2024)
The coronavirus (COVID-19) has emerged as one of the most serious issues. Scientists and administrators are thinking of employing a number of social distancing models to identify potentially infected people. Nevertheless, limited social distancing methods have been discovered for tracking, scheduling, and monitoring vehicles for smart buildings. In these methods, people are tested on a regular basis in testing facilities every few days. This suggests that there may be untested infected individuals exhibiting active symptoms. Furthermore, since pandemics comparable to COVID may exhibit a range of symptoms that fluctuate throughout the day. For this reason, each time a vehicle requests entry into the facility, a real-time test or check must be performed. This study proposes a real-time vehicle social distancing decision system for managing the number of vehicles (RT-VSDD) that adds an additional testing method besides the traditional testing phase (test reports from test centers) with a real-time vital health check at the building access request in order to reduce the risk of unidentified infected individuals. The concept of low-risk area and high-risk area in the building is introduced in this study where the method classifies the vehicles based on the risk levels and sends them to the targeted area. The system proposed in this study is identified as vehicle social distancing (VSD) system and is designed specifically for COVID pandemic. The performance evaluation of the proposed work has been performed using MATLAB simulations. 100 vehicles were assumed in the presented scenario with 5% untested, 20% positive, 75% negative, 30% high temperature, and 70% low temperature. When compared with the benchmark work, 40% of vehicles were classified as high risk and 55% were low risk by the proposed system, and 20% and 75% by the benchmark work. Only 5% of vehicles were denied access using the proposed system and 25% by the benchmark work. The total waiting vehicles rate was 25% and 11% in favour of the proposed work for a total waiting time of 100 minutes. The threshold value for the maximum vehicle allowed was reached 26 times by the proposed work against 13 times only by the benchmark work. 95% of vehicles were allowed access using the proposed technique, while only 75% were able to access the building using the benchmark technique. It is anticipated that the suggested system design will contribute to a decrease in the infection rate within buildings, reduces the negative economic impact, and manage the building access effectively for various industries and government sectors.